2005
DOI: 10.1080/10473289.2005.10464710
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Personal Exposure to Fine Particles in Toronto, Ontario, Canada

Abstract: Individuals are exposed to particulate matter from both indoor and outdoor sources. The aim of this study was to compare the relative contributions of three sources of personal exposure to fine particles (PM 2.5 ) by using chemical tracers. The study design incorporated repeated 24-hr personal exposure measurements of air pollution from 28 cardiac-compromised residents of Toronto, Ontario, Canada. Each study participant wore the Rupprecht & Patashnick ChemPass Personal Sampling System 1 day a week for a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
(60 reference statements)
4
10
1
Order By: Relevance
“…The median personal exposure to PM 2.5 in this study was comparable to levels reported from Boston , Seattle (Liu et al, 2003), and from Helsinki (Janssen et al, 2005;Lanki et al, 2007), but lower than levels reported from Minneapolis (Adgate et al, 2002), Toronto (Kim et al, 2005), Copenhagen (Sorensen et al, 2005), Vancouver (Ebelt et al, 2000), and Boston (Rojas-Bracho et al, 2004). Personal exposure to BS was lower than in Copenhagen (Sorensen et al, 2005), Helsinki, and Amsterdam (Janssen et al, 2005;Lanki et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The median personal exposure to PM 2.5 in this study was comparable to levels reported from Boston , Seattle (Liu et al, 2003), and from Helsinki (Janssen et al, 2005;Lanki et al, 2007), but lower than levels reported from Minneapolis (Adgate et al, 2002), Toronto (Kim et al, 2005), Copenhagen (Sorensen et al, 2005), Vancouver (Ebelt et al, 2000), and Boston (Rojas-Bracho et al, 2004). Personal exposure to BS was lower than in Copenhagen (Sorensen et al, 2005), Helsinki, and Amsterdam (Janssen et al, 2005;Lanki et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…Factors that influence personal exposures to ambient particulate air pollution have been investigated in several studies with repeated-measures designs via mixed-effects models (e.g., Janssen et al, 1998Janssen et al, , 2005Ebelt et al, 2000;Liu et al, 2003;Rojas-Bracho et al, 2004;Kim et al, 2005;Sorensen et al, 2005;Adgate et al, 2007;Lanki et al, 2007;Brown et al, 2009). However, only a few studies of environmental exposures to various air pollutants also reported between-person and within-person variance components for the study groups (e.g., Lee et al, 2004;Rappaport and Kupper, 2004;Egeghy et al, 2005;Lin et al, 2005;Sorensen et al, 2005;Lanki et al, 2007;Sarnat et al, 2009), two of these studies investigated exposure to PM 2.5 and BS (Sorensen et al, 2005;Lanki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, personal exposure to airborne substances is more closely related to indoor rather than outdoor pollution. 3,4 We review the sources, health effects and control strategies for several of the most important sources of residential biological and chemical contaminants.…”
mentioning
confidence: 99%
“…As listed in Table 2(a), personal OC ad EC concentrations measured in other developed countries usually have considerably lower values than Hong Kong, such as personal OC and EC ranging from 5.4 to 8.3 µg m -3 and 0.2 to 1.4 µg m -3 in the United State. (Wilson et al, 2000;Landis et al, 2001;Turpin et al, 2007;Brinkman et al, 2009); personal EC varied from 0.6 to 1.0 µg m -3 in Toronto and Prince George, Canada (Kim et al, 2005;Noullett et al, 2006). Individual's OC and EC exposure in urban cities of China were considerably higher than that in Hong Kong (Du et al, 2010;Zhang et al, 2015).…”
Section: Personal Exposure To Pm 25 and Carbonaceous Aerosolmentioning
confidence: 99%
“…The average personal PM 2.5 concentrations measured in the present study were compared with other studies (Table 2(a)). The average personal exposure to PM 2.5 measured in the developed countries show lower values than in Hong Kong, such as in American cities (ranging from 8.4 to 44.8 µg m -3 ) (Williams et al, 2000;Larson et al, 2004;Turpin et al, 2007;Brinkman et al, 2009), Canadian cities (varying from 18.0 to 22.0 µg m -3 ) (Kim et al, 2005;Noullett et al, 2006), and European cities (winter = 25.1 µg m -3 ; summer = 8.8 µg m -3 ) (Zmirou et al, 2000). In contrast, personal exposure to PM 2.5 measured in Chinese cities usually have higher values (ranging from 45.4 to 122.4 µg m -3 ) than that in Hong Kong.…”
Section: Personal Exposure To Pm 25 and Carbonaceous Aerosolmentioning
confidence: 99%